2014
DOI: 10.1016/j.jebo.2014.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Judgmental overconfidence and trading activity

Abstract: We investigate the theoretically proposed link between judgmental overconfidence and trading activity. In addition to applying classical measures of miscalibration, we introduce a measure to capture misperception of signal reliability, which is the relevant bias in the theoretical overconfidence literature. We relate the obtained overconfidence measures to trading activity in call and continuous experimental asset markets. Our results confirm prior findings that classical miscalibration measures are not relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Overconfidence can be separated in three facets; overconfidence about the certainty of information (miscalibration), overconfidence about ability (better-than-average effect) or overconfidence about performance on certain tasks (overestimation) (Moore & Healy, 2008). Whilst miscalibration is purported as the cause of overtrading (Daniel, Hirshleifer, & Subrahmanyam, 1998), studies have also shown this aspect of overconfidence, as measured by calibration questions, is unrelated to trading volume (Fellner-Röhling & Krügel, 2014;Glaser & Weber, 2007). Research has found that the better-than-average effect has more of an influence on trading frequency.…”
Section: Who Trades Frequently?mentioning
confidence: 99%
“…Overconfidence can be separated in three facets; overconfidence about the certainty of information (miscalibration), overconfidence about ability (better-than-average effect) or overconfidence about performance on certain tasks (overestimation) (Moore & Healy, 2008). Whilst miscalibration is purported as the cause of overtrading (Daniel, Hirshleifer, & Subrahmanyam, 1998), studies have also shown this aspect of overconfidence, as measured by calibration questions, is unrelated to trading volume (Fellner-Röhling & Krügel, 2014;Glaser & Weber, 2007). Research has found that the better-than-average effect has more of an influence on trading frequency.…”
Section: Who Trades Frequently?mentioning
confidence: 99%
“…3 To sum up, the better-than-average effect has been partially successful in predicting trade volume while miscalibration has been generally unsuccessful. Additionally, the better-than-average effect has been found to be more pronounced in men than in women (Bengtsson et al, 2005;Beyer, 1990;Beyer and Bowden, 1997;Niederle and Vesterlund, 2007), while miscalibration has not (Biais et al, 2005;Deaves et al, 2008;Fellner-Röhling and Krügel, 2014). Both of these facts suggest that the better-thanaverage effect is a more appropriate measure than miscalibration to try to explain the gender gap in trade volume.…”
Section: Measures Of Overconfidence In Financementioning
confidence: 99%
“…Many studies have found that decision makers with high confidence are likely to overestimate the accuracy of their judgment – a phenomenon called overconfidence (Lichtenstein et al , 1977; Doherty et al , 1979; Harvey, 1997; Klayman et al , 1999; Fellner and Krügel, 2012; Fellner-Röhling and Krügel, 2014; Thunström et al , 2015; Merkle, 2017). Moore and Healy (2008) and Bazerman and Moore (2008) found three principal forms of overconfidence: over-estimation of one’s actual performance; over-placement of one’s performance compared to others’; and over-precision about the accuracy of one’s judgment.…”
Section: Manifestations Of Bias In Cpdrmentioning
confidence: 99%